Factors influencing the likelihood of acceptance of postpartum intrauterine devices across four countries: India, Nepal, Sri Lanka, and Tanzania. (18th September 2018) - Makins, Anita; Taghinejadi, Neda; Sethi, Maya; Machiyama, Kazuyo; Thapa, Kusum; Perera, Gamini; Munganyizi, Projestine S.; Bhardwaj, Ajey; Arulkumaran, Sabaratnam
Abstract: Objective: To examine the factors that positively influenced the likelihood of accepting provision of postpartum intrauterine devices (PPIUDs) across four countries: Sri Lanka, Nepal, Tanzania, and India. Methods: Healthcare providers were trained across 24 facilities in counselling and insertion of PPIUDs as part of a large multicountry study. Women delivered were asked to take part in a 15‐minute face‐to‐face structured interview conducted by in‐country data collection officers prior to discharge. Univariate analysis was performed to investigate factors associated with acceptance. Results: From January 2016 to November 2017, 6477 health providers were trained, 239 033 deliveries occurred, and 219 242 interviews were conducted. Of those interviewed, 68% were counselled on family planning and 56% on PPIUD, with 20% consenting to PPIUD. Multiple counselling sessions was the only factor resulting in higher consent rates (OR 1.30–1.39) across all countries. Odds ratios for women's age, parity, and cadre of provider counselling varied between countries. Conclusion: Consent for contraception, specifically PPIUD, is such a culturally specific topic and generalization across countries is not possible. When planning contraceptive policy changes, it is important to have an understanding of the sociocultural factors at play. Abstract : Other than multiple counselling episodes, it was not possible to generalize across the countries on which factors positively influenced acceptance of PPIUD.